The Impact of Fetal Anomalies on Contemporary Labor Patterns - McCormick, Anna C.; McIntosh, Jennifer J.; Gao, Weihua; Hibbard, Judith U.; Cruz, Meredith O. (American Journal of Perinatology, 2019)
Objective To compare labor patterns in pregnancies affected by fetal anomalies to low-risk singletons.Study Design Labor data from the Consortium on Safe Labor, a multicenter retrospective study from 19 U.S. hospitals, including 98,674 low-risk singletons compared with 6,343 pregnancies with fetal anomalies were analyzed. Repeated-measures analysis constructed mean labor curves by parity, gestational age, and presence of fetal anomaly in women who reached full dilation. Interval-censored regression analysis adjusted for covariables was used to determine the median traverse times for labor progression.Results Labor curves for all groups indicated slower labor progress for patients with fetal anomalies. The most significant trends in median traverse times were observed in the preterm nulliparous and term multiparous groups. The median traverse times from 4 cm to complete dilation in the preterm nulliparous control versus anomaly groups were 5.0 and 5.4 hours (p < 0.0001).Conclusion Labor proceeds at a slower rate in pregnancies affected by anomalies.
Keywords: fetal anomalies; labor progress; labor curves; chromosome abnormalities